Study of (12Co–4Cr WC) and (Cr3C2–25NiCr) coatings sprayed by the HVOF process and subsequently laser remelted - Ana Claudia Costa Oliveira; Edinelson Carvalho; Paulo Dyer; Maria Margareth da Silva; Lucia Vieira; Carolina Hahn da Silveira; Getúlio de Vasconcelos (Materials Research)
The laser remelting technique on tungsten carbide (12Co–4Cr WC) and chromium carbide (Cr3C2–25NiCr) coatings deposited by HVOF provides improvements in surface properties, such as increased hardness and resistance to abrasive wear. This process uses a laser beam to selectively melt the coating, promoting a uniform and adherent layer. In the present work, tungsten carbide and chromium carbide alloy coatings were deposited on properly prepared SAE 1020 substrates using the high-speed oxy-fuel (HVOF) technique. After deposition, the coatings were remelted with a laser beam, varying the scanning speed and the laser beam power of the ytterbium fiber to obtain a pore- and crack-free coating and better metallurgical anchorage to the substrate. The samples were characterized by scanning electron microscopy (SEM), X-ray diffractogram, ASTM G132 Standard Test Method for Pin Abrasion Testing wear and microhardness. The results show that it was possible to obtain coatings with greater hardness after the laser remelting process, reducing pores or imperfections and metallurgically bonding to the substrate.